Elderly Care System by Using ARDUINO (NODE MCU) - Zaman Mahdi Abbas Alabbas , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The basic idea of this paper is to design a simple patient room containing a number of sensors like : heat and humidity sensor , distance sensor and fire sensor , where all these sensors are connected to node mcu esp8266, these devices monitored the patient status by internet of things technology (IOT) , and this project aims to make the nurse control a number of rooms at the same time from her room by monitoring the computer screen that display all the immediate patient’s information , and the nurses will here a warnning alarm when the patient will be at risk or make unwanted movement where he some times can not talk when the asthma attack . Also this monitoring system provides us with update medical records. Patients’ data are seen and advice is given from doctors to nurse to do what needed. So the data that will be collected is sent to the server there for the nurse and doctor will enter easily to the patient’s medical file and in this architecture we use a very available and not expensive equipments .This monitoring system is able to do monitoring patient’s that stay in hospital for a long time , by mobile , and that enable both doctor and nurse to avoid the repeatedly unnecessary visits to the patients and go to the most risky case through the monitoring screen .